2020
DOI: 10.1111/apt.16049
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: efficacy of balloon‐assisted enteroscopy for dilation of small bowel Crohn's disease strictures

Abstract: SummaryBackgroundEvidence for endoscopic balloon dilation of small intestinal strictures in Crohn's disease (CD) using balloon‐assisted enteroscopy is scarce.AimTo evaluate endoscopic balloon dilation for the treatment of small intestinal CD strictures using balloon‐assisted enteroscopy.MethodsCitations in Embase, MEDLINE, and Cochrane were systematically reviewed. In a meta‐analysis of 18 studies with 463 patients and 1189 endoscopic balloon dilations, technical success was defined as the ability to dilate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“…However, EBD has a poor therapeutic effect on patients with CD and prestenotic luminal dilatation, which often indicates a long‐term disease or high‐grade stenosis 81,83‐85 . In 2020, several retrospective studies indicated that EBD using balloon‐assisted enteroscopy could delay the recurrence and reduce surgical intervention in patients with CD and small bowel stricture, with a short‐term clinical efficacy of 82.3% and long‐term effective rate of 76.5%, as well as a low complication rate of 5.3% 86‐88 …”
Section: Treatmentmentioning
confidence: 99%
“…However, EBD has a poor therapeutic effect on patients with CD and prestenotic luminal dilatation, which often indicates a long‐term disease or high‐grade stenosis 81,83‐85 . In 2020, several retrospective studies indicated that EBD using balloon‐assisted enteroscopy could delay the recurrence and reduce surgical intervention in patients with CD and small bowel stricture, with a short‐term clinical efficacy of 82.3% and long‐term effective rate of 76.5%, as well as a low complication rate of 5.3% 86‐88 …”
Section: Treatmentmentioning
confidence: 99%
“…Numerous reports have documented the efficacy and safety of EBD in carefully selected cases [ 19 , 139 - 142 ]. EBD can improve symptoms and delay or obviate recourse to surgery [ 108 ].…”
Section: Introductionmentioning
confidence: 99%
“…Technical success was achieved in 90% and symptomatic relief was achieved in 80%; the complication rate was 2.8%. Nevertheless, almost 75% of the patients needed repeat dilation and 43% required surgery within 24 months [ 142 ]. A systematic review of SB dilation facilitated by DBE reported an 80% long-term success rate, with a complication rate of 2.6% per dilation and 4.8% per patient.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 75% of patients with CD ultimately undergo surgery at least once during their lifetime, and the main cause is strictures. 10 Stricture dilatation with BAE has been shown to have a high technical success rate (94.9%) and a low rate of major complications (5.3%). 10 Consistent with the result of previous reports, the study by Jeon et al 9 also showed a high technical success rate of over 80%.…”
mentioning
confidence: 98%
“… 10 Stricture dilatation with BAE has been shown to have a high technical success rate (94.9%) and a low rate of major complications (5.3%). 10 Consistent with the result of previous reports, the study by Jeon et al 9 also showed a high technical success rate of over 80%. 9 One of the most notable findings of this study is that the use of BAE related to small bowel strictures was significantly increased in the second period compared to that in the first period (2.9% vs 21.3%, p=0.002).…”
mentioning
confidence: 98%